Immunodetection and purification of recombinant human heat shock protein 47 - Ibrahim, Fatin Hazwani (2014)
Heat shock protein 47 (HSP47) is a protein that resides in the endoplasmic reticulum, with interaction specific to its substrate namely collagen. Recombinant human HSP47 gene (hhsp47) was transformed into E. coli BL21(DE3) and grown in Luria-Bertani (LB) growth medium. Protein expression was carried out at 20oC with induction using 0.1 mM isopropyl-ß-D-thiogalactopyranoside (IPTG). SDS-PAGE and Western blotting were performed to detect expression of hHSP47 in cell lysate and supernatant. The supernatant was then used for further applications such as immunoblotting and purification. In immunoblotting method optimisation, 5% (w/v) skimmed milk as blocking agent, 1 hour for blocking time, and 1:20000 secondary antibody concentration were empirically determined to have the most optimal detection with minimal background and high signal. For protein purification, affinity chromatography with the use of 1 mL HisTrapTM HP column was used. The purification yielded about 4 µM of around 80% purified hHSP47. SDS-PAGE analysis of the respective partially purified fraction shown a 47 kDa band, representing that hHSP47 was in monomeric form. Gelatin agarose pull down assay that aims to determine binding ability of hHSP7 to gelatin was performed before and after purification. The binding assay results indicates that hHSP47 still possesses its native folding after purification, leading to successful binding to gelatin